(untitled) (Third Sector Social Economic Review, 2023)
The aim of this study is to examine export behaviors of the companies producing in the construction machinery sector, to reveal the performance determinants that affect export behaviors and to create a new export decision-making model based on Pak’s (1991) model. The literature on the export behavior of the firm has been reviewed and it has been seen that the international orientation of the decision maker, the distinctive advantages of the companies, the internal and external environment are possible factors of the export performance of the firm. When the decision-making models in the literature are examined, it is stated that export decisions depend only on the internal and external environmental factors of the company. The effects of globalization are also included in the study. Information was collected through the questionnaire sent to the manufacturers and exporters of Construction Machinery. Data analysis methods used to analyze the obtained data and test hypotheses; exploratory factor analysis, confirmatory factor analysis and structural equation modeling (SEM). As a result of the research, it has been seen that global opportunities and risks affect the export behavior and decisions of companies and play a very important role in this process.